Evaluation of Preanalytical Conditions and Implementation of Quality Control Steps for Reliable Gene Expression and DNA Methylation Analyses in Liquid Biopsies. (4th January 2020) - Zavridou, Martha; Mastoraki, Sofia; Strati, Areti; Tzanikou, Eleni; Chimonidou, Maria; Lianidou, Evi
Abstract: BACKGROUND: Liquid biopsy provides important information for the prognosis and treatment of cancer patients. In this study, we evaluated the effects of preanalytical conditions on gene expression and DNA methylation analyses in liquid biopsies. METHODS: We tested the stability of circulating tumor cell (CTC) messenger RNA by spiking MCF-7 cells in healthy donor peripheral blood (PB) drawn into 6 collection-tube types with various storage conditions. CTCs were enriched based on epithelial cell adhesion molecule positivity, and RNA was isolated followed by cDNA synthesis. Gene expression was quantified using RT-quantitative PCR for CK19 and B2M . We evaluated the stability of DNA methylation in plasma under different storage conditions by spiking DNA isolated from MCF-7 cells in healthy donor plasma. Two commercially available sodium bisulfite (SB)-conversion kits were compared, in combination with whole genome amplification (WGA), to evaluate the stability of SB-converted DNA. SB-converted DNA samples were analyzed by real-time methylation-specific PCR (MSP) for ACTB, SOX17, and BRMS1. Quality control was assessed using Levey–Jennings graphs. RESULTS: RNA-based analysis in CTCs is severely impeded by the preservatives used in many PB collection tubes (except for EDTA), as well as by time to analysis. Plasma and SB-converted DNA samples are stable and can be used safely for MSP when kept at −80 °C. Downstream WGA of SB-converted DNA compensated for the limited amount of available sample in liquid biopsies. CONCLUSIONS: Standardization of preanalytical conditions and implementation of quality control steps is extremely important for reliable liquid biopsy analysis, and a prerequisite for routine applications in the clinic.